2014
DOI: 10.1002/bmc.3274
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution and excretion study of neopanaxadiol in rats by ultra‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry

Abstract: Neopanaxadiol (NPD), a major ginsenoside in Panax ginseng C. A. Meyer (Araliaceae), was reported to have neuroprotective effect. In this study, a method of ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC/QTOF-MS) was developed and validated for quantitative analysis of NPD in tissues, urine and feces, using liquid-liquid extraction (LLE) to isolate NPD from different biological samples, and chromatographic separation was performed on an Agilent Zorbax Stable Bond C18 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…We earlier reported liquid chromatography-tandem mass spectrometric (LC-MS/MS) methods for estimation of NPD, one of the aglycones of protopanaxadiol type ginsenosides, in a wide variety of matrices, including plasma, urine, feces, and different kinds of tissues. The methods were fully validated and applications were performed well for understanding systemic exposure and disposition of NPD [12][13][14]. Hence, the LC-MS/MS methods were developed in the present study to investigate the PK behaviors of ocotillol, RT 5 , and F 11 in rats and beagle dogs after oral administration for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…We earlier reported liquid chromatography-tandem mass spectrometric (LC-MS/MS) methods for estimation of NPD, one of the aglycones of protopanaxadiol type ginsenosides, in a wide variety of matrices, including plasma, urine, feces, and different kinds of tissues. The methods were fully validated and applications were performed well for understanding systemic exposure and disposition of NPD [12][13][14]. Hence, the LC-MS/MS methods were developed in the present study to investigate the PK behaviors of ocotillol, RT 5 , and F 11 in rats and beagle dogs after oral administration for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Drug metabolism studies play an increasingly important role throughout the entire drug discovery and development process as metabolites of administered drugs in biological fluids are vital for our understanding of drug safety and efficiency. The pharmacokinetics of NPD have been studied and reported by our laboratory . The data on an excretion study of NPD in rats after oral intake showed that less than 65% of the parent drug was recovered in feces and urine, which indicated biotransformations of NPD might exist in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…(A)) is one of the aglycones of PPD‐type ginsenosides, and was reported to have a neuroprotective effect and anti‐human colon carcinoma cell activity . Our previous study showed that the total NPD excretions in rats urine and feces were less than 65% dose of NPD; therefore, it is possible for metabolized products of NPD to exist in rats' bodies after oral dosage. Therefore, the metabolites and metabolic route of NPD in rats need to be explored, especially whether the epoxidation metabolic pathway is generated as well as metabolic profiles of PPD and PPT in rats.…”
mentioning
confidence: 99%
“…A total of 24 male C57/BL6J mice were divided into 4 groups at random, with 6 mice in a group for tissue distribution at 0.25, 1, 6, and 24 h. They were given YWS01125 after oral administration of 20 mg/kg, and then sacrificed at 0.25, 1, 6, and 24 h. Tissues from the heart, liver, spleen, lungs, kidneys, stomach, small intestine, colon, fat, muscle, testes, and brain were taken and rinsed with saline solution to remove the blood and connective tissues ( Geng et al, 2015 ; He et al, 2017 ; Jiang et al, 2017 ), then put on the filter paper and weighed, quickly. Each tissue sample was homogenized by using five times of the tissue weight saline (w/v).…”
Section: Methodsmentioning
confidence: 99%